2014
DOI: 10.1038/jcbfm.2014.133
|View full text |Cite
|
Sign up to set email alerts
|

Brain BDNF Levels Elevation Induced by Physical Training is Reduced after Unilateral Common Carotid Artery Occlusion in Rats

Abstract: We investigated the contribution of blood flow elevation in the cerebrovasculature to physical training-induced brain-derived neurotrophic factor (BDNF) levels elevation in the brain. Brain-derived neurotrophic factor protein levels were measured in the motor cortex 24 h after the last session of a forced treadmill walking (30 minutes a day, 18 m/minute for 7 consecutive days). Unilateral common carotid artery occlusion and modulation of exercise intensity (0 versus À 10% inclination of the treadmill) were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 39 publications
1
20
0
Order By: Relevance
“…, Banoujaafar et al . ) and the hippocampus (unpublished results) were reported by our laboratory to be higher in exercised than sedentary rats. These data combined with the present results indicate that changes in cerebrovascular BDNF translate into parallel changes in brain BDNF levels, indicating that BDNF produced by the cerebral microvessels ends up in the brain, at least for a large part.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…, Banoujaafar et al . ) and the hippocampus (unpublished results) were reported by our laboratory to be higher in exercised than sedentary rats. These data combined with the present results indicate that changes in cerebrovascular BDNF translate into parallel changes in brain BDNF levels, indicating that BDNF produced by the cerebral microvessels ends up in the brain, at least for a large part.…”
Section: Discussionmentioning
confidence: 66%
“…, Banoujaafar et al . ). It is noteworthy that our laboratory previously reported that the modalities of physical exercise and hypertension used in the present study respectively, increased and decreased BDNF levels in the heart and aorta (Prigent‐Tessier et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…EX consisted of a daily (30 min) walking activity (18 m/min) on a horizontal treadmill (model Exer-3/6; Linton Instrumentation, Norfolk, UK) for 7 consecutive days. We previously reported that this modality of EX resulted in a two-fold elevation in BDNF levels in the cortex (Quirie et al, 2012;Banoujaafar et al, 2014). Corresponding sedentary rats (SED) were kept in their cage in the vicinity of the treadmill.…”
Section: Modulation Of Cerebrovascular No Productionmentioning
confidence: 99%
“…Supporting a connection between brain BDNF levels and endothelium‐derived NO, the stroke‐induced rise in brain BDNF levels was reported to be lower in eNOS knock‐out animals than in wild‐type littermates (Chen et al ., ; Cui et al ., ). Likewise, pharmacological inhibition of NO synthases was shown to blunt the physical exercise‐induced elevation of brain BDNF levels (Chen et al ., ; Banoujaafar et al ., ). However, in the above studies, the presence of hypertension and the appearance of compensatory mechanisms in eNOS knock‐out mice (Ortiz & Garvin, ) as well as the use of a non‐selective NOS inhibitor complicated the interpretation of data.…”
Section: Introductionmentioning
confidence: 99%